Frozen Section Library: Pleura - Cagle, Philip T.; Allen, Timothy Craig; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Frozen sections are performed while a patient is undergoing surgery as a basis for making an immediate diagnosis that will impact treatment decisions. Frozen section diagnosis is often a highly demanding situation for the pathologist who must render a diagnosis quickly for the patient and surgeon. The Frozen Section Library series will provide concise, user-friendly, site specific handbooks that are well illustrated and highlight the pitfalls, artifacts and differential diagnosis issues that arise in the hurried frozen section scenario. Philip T. Cagle, MD, is Professor of Pathology, Weill Medical College of Cornell University, New York and Director of Pulmonary Pathology, The Methodist Hospital, Houston, Texas. Timothy Craig Allen, MD, JD, is the Chairman of the Department of Pathology, University of Texas Health Science Center at Tyler, Tyler, Texas.
Diffuse Malignant Mesothelioma -- Metastatic Cancers -- Other Primary Neoplasms of the Pleura -- Pleuritis and Pleural Plaque -- Uncommon Nonneoplastic Lesions of the Pleura -- Benign Reactive Proliferations vs. Malignancy.
Keywords: Medicine; Pathology; Medicine & Public Health; Pathology